Risk Assessment of Fire Hazards in Semarang City Residential Areas - Hari Murti, Raditya; Wijaya, Hendra Adi; Widuri, Indira Laksmi; Abda, Julmadian; Sophianingrum, Mada; Islami, Muhammad Rizki; Febriyanto, Ahady Farrel; Drestanta, Eduardo Erlangga (Universitas Negeri Semarang, 2023)
Based on data from the Semarang City Fire Department in 2013-2016, 1028 fire incidents took place in Semarang City. This incidence reached its highest in 2015 with 399 cases of fire which caused material losses of up to IDR 398.3 billion. Based on these figures, Semarang City possesses the highest incidence rate of fire cases in Central Java Province. However, studies on the risk and mitigation of fire hazard disasters in Semarang City still need to be carried out. This study aims to identify fire risks, to mitigate the disaster’s hazards in Semarang City, and to provide recommendations for arranging relevant buildings and the environment. The method used in this study is a qualitative descriptive method, in which interviews are conducted with key persons, with the utilization of GIS analysis to assess the risk of fire. The results of this study exhibit that in Semarang City, 14 villages have a high level of fire hazard risk, one of which is Rejosari Village which has the highest level of fire risk. This occurred mainly because historically, there have been many fire incidents in this area and even claiming several lives. The density of buildings and the difficulty of access further increase vulnerability in the case of fire. Nevertheless, the inhabitants still lack an understanding of this hazard. Accordingly, the fundamental mitigation to be carried out in Rejosari Village is to increase community comprehension and to consider the addition of fire protection and safety facilities, including hydrants, in densely populated buildings and areas, in order to reduce the risk of fire hazards.